Factors influencing upper gastrointestinal bleeding in geriatric coronary heart disease patients taking low-dose aspirin - Nisa, Shinta Khoirun; Mustofa; I Dewa Putu Pramantara Setiabudi (Indonesian Journal of Pharmacology and Therapy, 2025)
Geriatric patients are a special group that requires special attention in monitoring drug side effects. Low-dose aspirin use over an extended period of time increases the risk of upper gastrointestinal bleeding (UGIB). Identification of factors that influence UGIB is important to improve accuracy in selecting and monitoring drug therapy in geriatric patients. This study aimed to identify the variables that affect the incidence of UGIB in geriatric patients with coronary heart disease (CHD) who use antiplatelet. This study used a case-control design.Secondary data were obtained retrospectively from the medical records of CHD patients in the Dr. Sardjito General Hospital, Yogyakarta from January 2022 to June 2024. As cases were a group of inpatient CHD who received low-dose aspirin therapy and experienced UGIB, while as controls were outpatient CHD with the similar characteristics without UGIB. The data was analyzed using the Chi-Square and multiple logistic regression analysis. Bivariate analysis showed that hypertension (p = 0.003; OR 5.469; 95% CI 1.883-15.884) and the use of dual antiplatelet therapy/DAPT (p = 0.003; OR 10.075; 95% CI 2.052-49.469) were the risk factors that significantly affected the incidence of UGIB. However, further multivariate analysis demonstrated no single factor had the biggest impact on UGIB. In conclusion, risk factor that influence UGIB in the use of antiplatelet aspirin by geriatric patients with CHD are comorbid of hypertension and the use of DAPT.